Induced Biosynthesis of Formic Hydrogenlyase in Iron-Deficient Cells of Escherichia coli - Fukuyama, T. (1965)
Fukuyama, T. (University of Washington, Seattle), and E. J. Ordal. Induced biosynthesis of formic hydrogenlyase in iron-deficient cells of Escherichia coli. J. Bacteriol. 90:673–680. 1965.—Escherichia coli cells were grown aerobically on a lactate-mineral salts medium from which iron had been removed by extraction with 8-hydroxyquinoline and chloroform. These cells carried out induced biosynthesis of formic hydrogenlyase in a reaction mixture containing glucose, formate, and phosphate without the addition of amino acids, providing adequate amounts of iron salts were present. In the absence of iron, glucose was fermented and acids were produced, but no formic hydrogenlyase developed. When iron-deficient E. coli cells were repeatedly washed, the property of carrying out induced biosynthesis of formic hydrogenlyase with glucose, formate, phosphate, and iron was lost, but was restored on addition of acid-hydrolyzed casein to the reaction mixture. An energy source (provided as glucose) was necessary for enzyme production. Iron-deficient cells were devoid of hydrogenase and formic hydrogenlyase but showed formic dehydrogenase activity when adequate amounts of selenium and molybdenum were present in the growth medium. Hydrogenase was consistently absent in iron-deficient cells but appeared concomitantly with formic hydrogenlyase during induced biosynthesis of the latter in iron-deficient cells of E. coli.